La geografía: estado actual y perspectivas - Hernández Gurruchaga, Hilario (Investigaciones Geográficas: Una mirada desde el sur, 1982)
Present day geography is being a product of a scientific revolution. Theretore, it has been in an adaptative process during last years. This process includes theoretical quantitative and perceptual aspects (ecological paradigm). The present doy state of Geography shows that at the last quarter of century geographers have a new material and conceptual equipment, which contains: orientation toward problems solution, locational and ecological paradigms, philosophical modurity, integration to other sciences and disciplinary social relevance. With regard to Chilean Geography, i t was developed partly in isolation until the 70’ s. Then, i t began. a period of changes. In order to carry out tl em, three types of integration would have to be developed: paradigmatic, between traditional roots and new directions and between methods and problems.